THE EFFECT OF SERVICE QUALITY AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION AT PT. SYAHRIFAH ALAWIYYAH INSYRAH - Muhammad Fadli Hutabarat; Ihdina Gustina; Isra Rafika Sihombing (Universitas La Tansa Mashiro, 2026)
The Umrah travel service industry faces intense competition that demands companies to prioritize customer satisfaction as their primary advantage. This research is motivated by the decline in the number of pilgrims at PT. Syarifah Alawiyyah Insyirah by -24.91% in 2025. The main problems identified include the lack of optimal pilgrim assistance and minimal social interaction and a sense of family during the pilgrimage. The purpose of this study is to analyze the influence of service quality and customer experience on customer satisfaction, both partially and simultaneously. The research method used is a quantitative approach. The study population included 648 pilgrims in 2025, with a sample of 247 respondents determined using the Slovin formula and random sampling techniques. Data were collected through a Likert scale questionnaire and analyzed using the classical assumption test and multiple linear regression. The results showed that service quality (X1) had a positive and significant effect on customer satisfaction with a regression coefficient of 0.403. Customer experience (X2) also had a positive and significant effect with a coefficient of 0.322. Simultaneously, both variables significantly influence customer satisfaction with an F-value of 502.011. The coefficient of determination (R2) of 0.803 indicates that 80.3% of the variation in customer satisfaction is influenced by these two variables, while the remaining 19.7% is influenced by factors outside the model. Companies are advised to improve the professionalism of their assistance and create a warmer travel atmosphere to strengthen pilgrim loyalty.